Effect of Copper Cobalt Oxide Composition on Oxygen Evolution Electrocatalysts for Anion Exchange Membrane Water Electrolysis - Kwon, Chae-Yeon; Jeong, Jae-Yeop; Yang, Juchan; Park, Yoo Sei; Jeong, Jaehoon; Park, Honghyun; Kim, Yangdo; Choi, Sung Mook (Frontiers in Chemistry, 2020)
Copper cobalt oxide nanoparticles (CCO NPs) were synthesized as an oxygen evolution electrocatalyst via a simple co-precipitation method, with the composition being controlled by altering the precursor ratio to 1:1, 1:2 and 1:3 (Cu:Co) to investigate the effects of composition changes. The effect of the ratio of Cu2+/Co3+ and the degree of oxidation during the co-precipitation and annealing steps on the crystal structure, morphology, and electrocatalytic properties of the produced CCO NPs were studied. The CCO1:2 electrode exhibited an outstanding performance and high stability owing to the suitable electrochemical kinetics, which was provided by the presence of sufficient Co3+ as active sites for oxygen evolution and the uniform sizes of the NPs in the half cell. Furthermore, single cell tests were performed to confirm the possibility of using the synthesized electrocatalyst in a practical water splitting system. The CCO1:2 electrocatalyst was used as an anode to develop an anion exchange membrane water electrolyzer (AEMWE) cell. The full cell showed stable hydrogen production for 100 h with an energetic efficiency of >71%. In addition, it was possible to mass produce the uniform, highly active electrocatalyst for such applications through the co-precipitation method.